Calculation of the moments and cumulants of the discrete renewal process - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене. Вычисление моментов в семиинвариантов дискретного процесса восстановления A. Aleškevičienė. Diskretinio atstatymo proceso momentų ir semiinvariantų išskaičiavimas